Influence of employee-focused corporate social responsibility on the turnover intention of employees in small and medium-sized enterprises - Bonaventure, Okolocha Chizoba (2016)
The purpose of this research paper is to investigate employee turnover intention among small and medium- sized enterprises in Malaysia (SMEs), where difficulty in retention of employees is recognized as a major issue for SME managers. This study seeks to determine the mediation effect of employer brand on employee-focused corporate social responsibility (CSR) and turnover intention. This study uses positivism through a self-administered questionnaire survey with 498 respondents among small and medium-sized enterprises in Selangor, Wilayah Persekutuan Kuala Lumpur, and Johor. This study is significant in a few ways: Firstly, the findings support the relationship between employee-focused CSR and turnover intention. Secondly, employee-focused CSR was found to positively affect perceived employer brand. Thirdly, perceived employer brand was positively related to job satisfaction but the relationship was found not to be statistically significant. However, the relationship between perceived employer brand and organization identification was positive and statistically significant. Fourthly, job satisfaction and organization identification were found to significantly and negatively affect turnover intention. Lastly, the mediating role of perceived employer brand on employee-focused CSR and turnover intention relationship was significant. The implications of this study from both theoretical and managerial perspective were discussed. The study findings are expected to guide SMEs manager and policy makers on employee related decisions and also provide them with insight on the benefits that could be derived from employee focused CSR. Limitations and directions for future research are also discussed.